2002
DOI: 10.1128/cdli.9.6.1165-1168.2002
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and Killing of Bacteria by Professional Phagocytes and Dendritic Cells

Abstract: Dendritic cells (DC) represent a class of professional antigen-presenting cells whose primary function is to alert the immune system, not to clear invading microorganisms. The objective of our study was to compare the abilities of polymorphonuclear neutrophilic leukocytes (PMN), monocytes, monocyte-derived macrophages (MDM), monocyte-derived immature DC (imDC), and mature DC (maDC) to ingest and destroy Staphylococcus aureus and Escherichia coli. Acridine orange staining and fluorescence microscopy demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
70
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 20 publications
6
70
1
Order By: Relevance
“…This infection rate is higher than that reported for other intracellular pathogens, such as Leishmania major, where amastigotes infect only 36% of fetal skin-derived DCs at 18 h after inoculation (45). Unlike professional phagocytes, the major function of DCs is not to clear pathogens but to present antigens to the immune system (37). Quantification of intracellular rickettsiae in BMDCs (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…This infection rate is higher than that reported for other intracellular pathogens, such as Leishmania major, where amastigotes infect only 36% of fetal skin-derived DCs at 18 h after inoculation (45). Unlike professional phagocytes, the major function of DCs is not to clear pathogens but to present antigens to the immune system (37). Quantification of intracellular rickettsiae in BMDCs (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…In agreement with this finding, Aline et al (10) have demonstrated that the intracellular replication of Toxoplasma gondii in DC is inhibited by an oxygen-dependent mechanism. Thus, even if DC might have a reduced ability to kill pathogens when compared with professional phagocytes (60), these cells posses the ability to clear intracellular pathogens by an oxygen-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…at the onset of infection in the two types of cells. Phagocytic activities of macrophages and immature DCs have not often been compared; moreover, conflicting conclusions have been reported (17,22,31). Macrophages and DCs were infected with B. suis; in parallel, the phagocytosis of 1 m latex beads or B. suis manB was analyzed as a control.…”
mentioning
confidence: 99%